The Influence of Digitalization on the Managerial Decision-Making Process in International Business - Hrynchak N. А.; Horobets О. О. (Statistics of Ukraine, 2024)
Digitization of international business is changing the emphasis of perception of the role and decision-making process in every field of international business activity. The article examines the impact of digitalization on the decision-making process in international business. It is substantiated that the introduction of digital technologies in the decision-making process is due to the large amount of data and factors that need to be analyzed in the decision-making process, and the dynamic development of the digital ecosystem in which the international enterprise functions. Digitization and digital transformation of international business activities can ensure business efficiency due to accelerated decision-making with the help of digital management decision-making technology. It was determined that the digital technology of management decision-making is based on the use of information and computer technologies, digital tools, information systems and databases in the decision-making process. Features and areas of application of the most popular digital tools, such as artificial intelligence and machine learning, smart sensors, Business Intelligence (BI) tools, decision support systems, data visualization tools, project management tools, collaboration tools, Customer Relationship Management (CRM) tools, Enterprise Resource Planning (ERP) Systems, was characterized at different stages of the decision-making process. It is substantiated that the integration of digital tools in managerial activities improves the decision-making process, making it more efficient, accurate and scalable. The advantages of using artificial intelligence in the decision-making process in international business are singled out. It was noted that when implementing and using digital tools in the decision-making process, international enterprises should have an appropriate data management policy and pay attention to security measures to ensure the integrity of the technological decision-making process in international business